Prototype Aplikasi SI-Warga Sebagai Penunjang Administrasi Surat Pengantar dan Iuran Warga pada Rukun Tetangga - Ani Oktarini Sari; Ishak Kholil (Infotek: Jurnal Informatika dan Teknologi, 2022)
The use of information technology to support administrative activities in the neighborhood makes it easier for administrators to provide administrative services for community members. The service of making rt cover letters and paying residents' mandatory contributions at RT08 / RW10 Perum Ambar Cibinong Residence Bogor still uses conventional methods, namely by recording manually. This process is considered inefficient in the process of waiting for the process of checking and making letters. And for the payment process that is still carried out by paying directly to the public relations and then handed over to the Treasurer of the RT. For this reason, an information system is needed that can facilitate these problems. The service of requesting a letter of introduction and payment of mandatory dues can be facilitated through the SI-Warga application. The creation of a SI-Warga application using a prototype model, where the flow and stages used include identifying users and developing prototypes. With this web-based application, it is hoped that the documentation of the cover letter archive and reports on the payment of mandatory contributions for residents will be more organized and well stored and can be accessed anywhere when needed with an internet connection.